Those at Home, Those in the Yard. (Jerusalem : The Israel Museum, 1993)
Shachar, Gil ; Shir, Zvi ; Shapir, Michael ; Mizrachi, Rachela ; Ziv, Neta ; Slabosky, Pesach ; Moshe, Dan ; Tzaig, Uri ; Levy, Smadar ; Rubinstein, Hugit ; Elnekaveh, Daniel
Those at Home, Those in the Yard, The Israel Museum, Jerusalem, 1993
boek